3D phonograms book / Mohd Abqari Ayob and Norfadilah Kamaruddin - Ayob, Mohd Abqari; Kamaruddin, Norfadilah (Research Innovation Business Unit, 2014)
Much of the heritage preservation work is done at the national, regional, or local levels of society in Malaysia. Therefore limited work has been carried out in the context of conserving local popular artist in Malaysia such as P. Ramlee, Nordin Ahmad, Siput Serawak, Jins Shamsuddin, Mat Sentul, Saloma, Sudirman etc in the form of printed book, an autobiography or even a video documentary. Thus, in telling the story or history of these local popular artist that are almost completely lost, a new experience of reading a printed book was used through new media technology application (3d technique/ approach that usually used in sequential video and movie by viewing phonograms images). Introduction 3D phonograms book is a documentation an autobiography in telling the story or history of these local popular legendary artist that are almost completely lost, with a new experience of reading using a stereoscopic imaging, is a technique used to enable a three dimensional effect, adding an illusion of depth to a flat image. The perspective difference between objects seen by presenting two separate images, which is one for the right eye, and one for the left are incorporated through the use of specialized glasses. Denoting a process by which two photographs of the same object taken at slightly different angles is viewed together, creating an impression of depth and solidity. Many of the picture that have been shown on the book, internet and others about the local Malaysian legendary artist are normal photograph the book is not attractive, nowadays children love an interactive, attractive and unique things. This 3D phonograms book is using an anaglyph picture or known as a stereoscopic picture to attract the reader and also it can give more impact because of the anaglyph picture can show the depth in the picture and also a new experience. The significance of this 3D phonograms book is it can attract the students and children love to read the book because the book is attractive. Commercialisation of potential 3D phonograms book has the potential to be commercialised because it has its own unique aesthetics value for those interested in and studying the local Malaysian legendary artist’s in new ways. This 3D phonograms book also can be made depicting prominent public figures in history books to be used in school.